Entre a patrimonialização e a incompreensão: Propostas para o tombamento histórico e cultural do conjunto urbano do bairro Lagoinha, Belo Horizonte - Pereira, Márcio Mota (Temporalidades, 2020)
In the municipality of Belo Horizonte, Brazil, the Directorate of Cultural Heritage (Diretoria de Patrimônio Cultural) of the Municipal Foundation of Culture (Fundação Municipal de Cultura), is responsible for the management of historical and cultural heritage, limited to the territoriality of the Minas Gerais state capital. In the year 2016, this public body increased its role in ensuring the heritage preservation of historic buildings located in the Lagoinha neighborhood, a region that over the past decades has been impacted by various urban changes, in addition to others, of a social nature. Far from seeking answers to the questions that involve the listing of buildings in the region by the government, it is the objective of this research to check with its residents which factors, circumstances or even instances are deficient in what is proposed, as well as the reflection and the meaning of the heritage listing for them.